Successful use of snare electrocautery via flexible fiberoptic bronchoscopy for removal of an endobronchial hamartoma causing chronic lung atelectasis and mimicking malignancy - Chao Liu (Therapeutic Advances in Respiratory Disease, 2017)
We present a rare case of giant endobronchial hamartoma coexisting with lung atelectasis for more than 3 years. The small specimen initially biopsied via bronchoscope did not reveal tissue features, but some features were suspicious for squamous cell carcinoma. The lesion was removed completely using snare electrocautery combined with argon plasma coagulation via flexible fiberoptic bronchoscopy. The patient made a satisfactory recovery, and a pathological diagnosis was made. This could be a useful option in selected endobronchial tumors.